Advancements in Rechargeable Zn-Air Batteries with Transition-Metal Dichalcogenides as Bifunctional Electrocatalyst - Gupta R.K.; Maurya P.K.; Mishra A.K. (My University, 2025)
This review covers recent progress on transition metal dichalcogenides (TMDs) as bifunctional electrocatalysts for Zinc-air batteries (ZABs), emphasizing their suitable surface area, electrocatalytic active sites, stability in acidic/basic environments, and tunable electronic properties. It discusses strategies like defect engineering, doping, interface, and structural modifications of TMDs nanostructures for enhancing the performances of ZABs. Zinc-air batteries are promising energy storage devices owing to their high energy density, low cost, and environmental friendliness. However, the development of durable and efficient bifunctional electrocatalysts is a major concern for Zn-air batteries. In this review, we summarize the recent progress on transition metal dichalcogenides (TMDs) as bifunctional electrocatalysts for Zn-air batteries. We discuss the advantages of TMDs, such as high activity, good stability, and tunable electronic structure, as well as the challenges, such as low conductivity, poor durability, and limited active sites. We also highlight the strategies for fine-tuning the properties of TMDs, such as defect engineering, doping, hybridization, and structural engineering, to enhance their catalytic performance and stability. We provide a comprehensive and in-depth analysis of the applications of TMDs in Zn-air batteries, demonstrating their potential as low-cost, abundant, and environmentally friendly alternatives to noble metal catalysts. We also suggest future directions like exploring new TMDs materials and compositions, developing novel synthesis and modification techniques, investigating the interfacial interactions and charge transfer processes, and integrating TMDs with other functional materials. This review aims to illuminate the path forward for the development of efficient and durable Zn-air batteries, aligning with the broader objectives of sustainable energy solutions. © 2024 Wiley-VCH GmbH.